The effective use of technology in international education classrooms to enhance and transform learning - Paul Walton MSc (Mathematical Statistician and Engineering Applications, 2023)
Technology’s pervasiveness has a wide range of positive and negative effects on society, which extends to the field of education. The manner that material is presented and taught in the classroom has been significantly altered by technology; this essay focuses on elaborating on those implications (Jabbarov, 2020). Education has transformed thanks to technology. While professors utilize technology to increase the impact of the teachings, students have computers and other devices to aid with college work and simple access to research tools and other relevant information. MOOCS (Massive online open courses), have grown considerably through the use and accessibility of technology. Class central (2021) state that there has been an increase form 330,000 learners to over 220 million in the last 10 years., in 2021, 40 million users signed up for a course. Technology, however, makes it possible for students from all nations to participate in online activities that ensure research sharing. An article by Campustechnology (2017), stated that over 94% of students actively want to use their smartphones in education to collaborate, research and complete their studies. They believed it helped them to have greater ability to ‘learn and retain information’.